PELAKSANAAN TATA RUANG (TATA LETAK, TATA UDARA, TATA WARNA, DAN TATA CAHAYA) TERHADAP EFEKTIVITAS KERJA (UKURAN WAKTU, BIAYA, & KETELITIAN) PADA RUANG REKAM MEDIS DI RUMAH SAKIT IBU DAN ANAK BUDIASIH SERANG - Abdul Rauf Chaerudin; Wahyu Widodo (LP2M Universitas Bina Bangsa, 2021)
This research aims to find out the implementation of spatial planning on the effectiveness of employee work in the medical record room RSIA Budiasih Serang. In this study the method used is a descriptive research method with data collection techniques and the dissemination of questionnaires to a number of respondents. Respondents in this study were employees in the medical record room RSIA Budiasih. The population in this study amounted to 30 people with a sample of 30 people. While the data analysis is done with the formula product moment. The implementation of spatial arrangements has a positive and very real effect on the Effectiveness of Work in the medical record room rsia Budiasih. Based on the results of the research outlined in the previous chapter the results of the hypothesis obtained regression equation:Y = 7.686 + 1.142X,which means that if the spatial implementation variable (X) is worth zero, then the value of the work effectiveness variable (Y) is 7,686. And every increase in spatial implementation by one unit, the effectiveness of work will increase by 1,142 units. From the results of the analysis with the help of the SPSS program, the correlation coefficient value of 0.992 and the result of the calculation of the coefficient of determination (R²) = 0.984. From the results of the calculation of the coefficient of determination of 98.41%, which shows the magnitude of the effectiveness of employee work 98.41% influenced by spatial implementation, while 1.59% is influenced by other factors not described in this study. Based on descriptive results, the percentage can be known that the variables of spatial implementation have a positive and significant effect on the effectiveness of employee work evidenced by t-count = 41,134 and t-table = 1,701 which means t-calculate> t-table so that the improvement of spatial implementation will increase the effectiveness of employee work.